Benzodiazepine receptor distribution and diazepam binding in schizophrenia: an exploratory study - Schröder, Johannes; Bubeck, Bernd; Demisch, Sibylle; Sauer, Heinrich (Psychiatry research, 1997)
Clinical studies indicate that patients with acute schizophrenia may benefit from benzodiazepine treatment. Therefore we investigated the benzodiazepine receptor distribution and diazepam binding in 20 patients with DSM-III schizophrenia using single photon emission computed tomography (SPECT) with iomazenil as the ligand. In each patient, two SPECT images were obtained: SPECT 1 was obtained 2 h after intravenous injection of 200 MBq I-123-iomazenil. Following SPECT 1, patients received 10 mg diazepam intravenously. Twenty min later, SPECT 2 was started. The highest iomazenil uptake was found in the occipital cortex followed by the frontal and temporal cortices. Baseline iomazenil uptake in the medial frontal cortex was significantly (P < 0.05) correlated with the BPRS total score (r = 0.46). Diazepam injection led to a significant activity decrease in iomazenil binding which was greatest in the frontal regions of interest. With respect to the medial frontal cortex, this effect was significantly (P < 0.05) more pronounced in patients with a remitting than a chronic course of the disorder. These findings suggest that changes of the benzodiazepine receptor system in the frontal cortex may be associated with severity and chronicity of schizophrenia.